Kemandirian dan Efektivitas dalam Melaksanakan Otonomi Daerah Kabupaten dan Kota di Provinsi Kalimantan Selatan - Putera , Muhammad Faisal Perdana (PPJP ULM, 2019)
The purpose of this study is to examine the performance of regional finance at the district and municipal governments in South Kalimantan province based on the independence and effectiveness of regional finance period 2012 to 2016 as well as the trend of regional financial effectiveness and effectiveness period 2012 to 2016. The type of research used is descriptive, Regency, and City in South Kalimantan Province and the sample of all districts and cities in South Kalimantan Province. Secondary data were obtained from the Regional Finance Board of South Kalimantan Province and Directorate General of Balance of Ministry of Finance. Analytical techniques used are the ratio of independence and local financial effectivity and percentage trend of independence and effectiveness of regional finance. The results obtained in this study are: 1) The ratio of regional autonomy in general in 2012 to 2016 into a deficient category. 2) The effectiveness ratio of local finance in general from 2012 to 2016 is effective except the Upper River Central Regency is in a balanced category 3) The trend of regional autonomy has a good development unless the Regency of Banjar in 2015 and 2016 is below 100 percent. 4) Trend of regional financial effectiveness from 2013 until 2016 tends to have a positive trend. There are four areas and tend to experience negative trend direction. There is 8 area.